Role of dual energy X-ray absorptiometry scan for assessing bone mineral density in patients with chronic plaque psoriasis: a cross-sectional study - N., Revathi T.; Sajjanshetty, Maheshwari (International Journal of Research in Dermatology, 2019)
Background: Psoriasis is a T cell mediated chronic inflammatory disorder of skin, joints and immune system. Data regarding possible association between psoriasis and reduced bone mineral density are limited and hence association is not fully conclusive. Systemic inflammatory cytokines in the psoriasis have been identified in the pathogenesis of reduced bone mineral density. Among various available methods, Dual X-ray absorptiometry (DXA), found to be gold standard for assessing bone mineral density. Methods: An observation study of 30 patients with chronic plaque psoriasis aged between 18 years to 50 years fulfilling the criteria were enrolled and studied. Dual energy X-ray absorptiometry scan (DEXA) of left forearm radius (non-dominant hand) was done. T score was calculated and bone mineral density assessed based on WHO criteria. Using software SPSS version 24, Pearson’s correlation and linear regression analysis applied. Results: Out of 30 patients, there were 18 males and 12 females. Mean age of patients 37.93 years. Majority of the psoriatic patient showed osteopenia on DEXA scan and significant positive correlation was found between duration of psoriasis disease (r=0.34, p=0.03), body surface area percentage (r=0.36, p=0.04) and body mass index (r=0.32, p=0.02). Conclusions: Early identification of reduced bone mineral density in patients with psoriasis particularly in those with longer duration of the disease, involving large body surface area (more than 10) and with higher body mass index by DEXA scan helps to reduce osteoporotic fracture and other associated comorbidities.